Advanced separation methods for collagen parent alpha-chains, their polymers and fragments - Deyl, Z; Miksík, I (Journal of chromatography. B, Biomedical sciences and applications, 2000)
Current techniques used for collagen alpha-chains and their CNBr fragments are reviewed. Ion exchange, gel permeation, reversed-phase and affinity chromatography are discussed mainly from the preparative aspects as these are both the techniques of choice to remove biological matrix contaminants always present in collagen preparations and techniques routinely used for preparative purposes. Among electromigration procedures gel electrophoresis is widely used both for intact collagen alpha-chains and their fragments. Recently this technique was applied also for miniaturised preparations. Immunoblotting techniques serve more specific detection of otherwise hard to distinguish different collagen polypeptide chains. Capillary electromigration techniques brought recently new aspects of understanding the behaviour of collagen proteins upon different separation modes and seem to represent a smart perspective for better quantitation of individual collagen species.
Keywords: kolagen; Peptide Fragments; Chromatography, High Pressure Liquid; elektroforéza; zvířata; bromkyan; Humans; Cyanogen Bromide; Electrophoresis; Collagen; peptidové fragmenty; vysokoúčinná kapalinová chromatografie; lidé; Animals